Peran Sustainability Reporting pada Kinerja Keuangan dan Nilai Perusahaan - Endiana, I Dewa Made; Sunarsih, Ni Made (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2025)
Sustainability reporting is the practice of measuring, disclosing and accountability efforts for organizational performance in achieving sustainable development goals to stakeholders both internal and external. This research aims to analyze the influence of Sustainability Reports on Financial Performance as proxied by Current Ratio (CR), Return on Assets (ROA), Earning per Share (EPS) and Company Value as measured by Tobin's Q in non-financial companies listed on the Indonesia Stock Exchange in 2021-2023.The population in this research is 376 non-financial companies listed on the Indonesia Stock Exchange in 2021-2023. The sample for this research was 35 companies determined based on the purposive sampling method. The analysis technique used in this research is Simple Linear Regression.The results of this research show that the Sustainability Report on Financial Performance which is proxied by the Current Ratio (CR), Return on Assets (ROA), Earning per Share (EPS) and firm value has a positive effect.